Buddhist Way of Wellbeing: Developing of Organizations Related to the Creative, Buddhist Way of Wellbeing for Development the Quality of Life of Thai Population and Thai Society - Panyachit, Saichol; Phrasuthirattanabundit; Wanitchanon, Phoobade; Phramaha Chutupak Aphinandho (Connexion: Journal of Humanities and Social Sciences, 2023)
The pandemic situation has caused changes in the paradigm of health development in terms of social relationship structures, medicine and public health management systems and new digital technological ecology. This research aimed to (1) learn lessons from the roles of the people’s training units in Tambon (Sub-district) in improving the quality of life of Thai people; (2) develop innovation in communicating the Buddhist way of wellbeing to create wider contentment in Thai society; (3) and to develop a policy-oriented proposal for development of wellbeing through organizations related to the create, Buddhist way of wellbeing. The research methodology involved collaborative research workshops of forty-five people’s training units in the Tambon. Following this, the work operations of those units were studied and the information gained was analyzed by means of content analysis as well as domain analysis. The research found that the role of the people’s training units in the Tambon and their promotion of the quality of life were apparent in four groups of monks. The first group consisted of those monks who were determined to take care of people’s health; the second group consisted of monks who were determined to increase skills and the welfare for the community; the third group was involved with the monks who were determined to prevent disaster and unexpected situations; and the fourth group contained monks who were determined to conserve local traditions and ways of life and promote a pluralistic cultural society. An innovative communication of the Buddhist wellbeing ways for Thai society could be developed through “CHEWA” model, which emphasizes health communication for health awareness raising. As for the policy-oriented dimension to develop people’s wellbeing related to Buddhist way of wellbeing organization, the internal strength of the groups of monks must be promoted, and the external strength as well. This included the combination of work operations and collaborations in the form of networks, which be enable the Buddhist way of wellbeing organization to continue working in a sustainable way in the future.